(untitled) (diségno, 2019)
Jorge Llopis Verdú’s book begins with a Hadot and Heiddeger’s quote, defying the reader to recognize the usefulness in the useless, so that he could keep pursuing this useful exercise boldly. This refection on drawing starts from an investigation into its own usefulness and its historical role as a privileged scientifc language. It has indeed been used as a powerful tool to record the travel experiences –since the first explorations– ending up generating the computer graphics and some of the new visual arts. This is the reason why the present book is particularly appropriate for the times: it proposes an updated report of the issues related to the architectural representation and how to teach it, based on the analysis of previous studies that define the bibliographic pantheon of our academic field. (read more)